Programme Leads' Address - Sara Namvar, Matthew Jones, Tahmina Hussain (BioScientist: The Salford Biomedicine Society Magazine, 2025)
<p class="MsoNormal" style="margin-bottom: 12pt; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Hear from the Biomedicine Programme Leads at the University of Salford, as they welcome students, returning and new. Explore the achievements of the Biomedicine Department and discover what to look forward to, in this academic year.